The value of paleolimnology in reconstructing and managing ecosystem vulnerability: a systematic map - Victoria Theresa Watson; Andrew Scott Medeiros (Canadian Science Publishing, 2021)
Vulnerability can measure an ecosystem's susceptibility to change as a result of pressure or disturbance, but can be difficult to quantify. Reconstructions of past climate using paleolimnological methods can create a baseline to calibrate future projections of vulnerability, which can improve ecosystem management and conservation plans. Here, we conduct a systematic map to analyze the range and extent that paleolimnological published studies incorporated the concept of vulnerability. Additional themes of monitoring, management, conservation, restoration, or ecological integrity were also included. A total of 52 relevant unique articles were found, a majority of which were conducted in Europe or North America since 2011. Common themes identified included management and adaptation, with the latter heavily focussed on climate change or disturbance. From this, we can infer that the use of paleolimnology to discuss the concept of vulnerability is an emerging field. We argue that paleolimnology plays a valid role in the reconstruction of ecosystem vulnerability due to its capacity to broaden the scope of long-term monitoring, as well as its potential to help establish management and restoration plans. The use of paleolimnology in vulnerability analysis will provide a clearer lens of changes over time; therefore, it should be frequently implemented as a tool for vulnerability assessment.